Socio-Economic and Regional Determinants of EU Ignorance in Turkiye - Mücahit Aslan (Journal of Economy Culture and Society)
The European Union is mostly criticized for its so-called democracy deficit. To tackle this, citizens are expected to have information about European integration so that they can make conscious choices. Nevertheless, it has been well documented in research conducted over the years that EU citizens are generally ignorant of the EU. This study aims to investigate the factors underpinning the lack of EU knowledge. Although socio-economic and demographic factors affecting EU ignorance in European countries have been investigated in previous studies, the factors affecting the EU knowledge level of Turkish people has only been examined in one study in the literature, which failed to include the regions (cities) variable. To close this gap, this research examines the effects of regions (cities) in Turkey on the EU ignorance by controlling for other variables frequently mentioned in previous research. In order to run the analysis, data from Eurobarometer 93.1 and 94.3 surveys were used and binary logistic regression was employed as a method of analysis because of the dichotomous nature of the dependent variable. The results of the two regression models show that citizens living in cities such as Istanbul, Ankara, Antalya, and Gaziantep are less likely to be ignorant of the EU than those living in other cities. Moreover, in both models, the regions (cities) variable is a stronger factor than factors such as age, education, occupation, gender, and political opinion.